Credit Constraints, Quality, and Export Prices: Theory and Evidence from China - Haichao Fan; Edwin L.-C. Lai; Yao Amber Li (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper examines the relationship between the credit constraints faced by a firm and the unit value prices of its exports. The paper modifies Arkolakis's (2010) model of trade with heterogeneous firms by introducing endogenous quality and credit constraints. The model predicts that tighter credit constraints faced by a firm reduce its optimal prices as its choice of lower-quality products dominates the price distortion effect resulting from credit constraints. However, a competing theory based on the alternative assumption that quality is exogenous across firms would predict completely opposite results: Prices increase as firms face tighter credit constraints. An empirical analysis using Chinese bank loans data, Chinese firm-level data from the National Bureau of Statistics of China (NBSC), and Chinese customs data strongly supports the predictions of the endogenous-quality model. Moreover, the predictions of the exogenous-quality model are supported by using quality-adjusted prices in regression analysis. In addition, we confirm the mechanism of quality adjustment: firms optimally choose to produce lower-quality products when facing tighter credit constraints.
Keywords: F10; F30; D20; G20; L10; 330; credit constraints; credit access; credit needs; endogenous quality; export prices; quality; heterogeneous firms; productivity